Enhancing Speaking Skills through EngBreaking: A Revolutionary Language Learning Platform - Fiqhiyatul Khakimah (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Mastery of speaking skills in a foreign language is a major challenge for many language learners. To address this challenge, a revolutionary new language learning platform called EngBreaking has emerged. EngBreaking combines innovative approaches and advanced technology to enhance speaking skills in English. Through interactive speaking practice sessions, games, and real-time feedback, EngBreaking enables learners to practice speaking confidently and acquire the skills needed to communicate effectively in real-life situations. This research examines the role of EngBreaking in improving foreign language speaking skills and its potential impact on language learners at various proficiency levels. Data were collected through questionnaires involving 50 students at BASMAH Dormitory. The results indicate a significant improvement in English speaking abilities, with high scores in many aspects: 70% regarding the quality of the EngBreaking platform, 65% of respondents experienced an increase in English language skills, and 75% were satisfied with the EngBreaking platform service. Based on the questionnaire score results, it can be concluded that the use of the EngBreaking platform effectively enhances English speaking skills. This suggests that EngBreaking not only boosts confidence and speaking skills but also expands vocabulary and grammar understanding. The implications of these findings are that EngBreaking has great potential to change the paradigm of language learning and provide broader access for learners to achieve higher proficiency levels in foreign languages.